Docência e inclusão: reflexões sobre a experiência de ser professor no contexto da escola inclusiva - Duek, Viviane Preichardt (2006)
The present study is inserted in the research line of special education, circumscribed to the Program of Post-Graduation in Education of the Federal University of Santa Maria, Brazil. This qualitative research had as main objective to understand the experience of being professor within the context of the inclusive school, investigating the way professors of regular classes perceive the reality of working with students with special educational needs (SSEN). Data was collected using interviews and observations with six teachers of basic education of a public state school at Santa Maria, RS, who work with SSEN. The analysis were based on the Person Centered Approach (PCA), including its relevant factors, such as the concept of self, central element of the theory of personality of Carl Rogers, who, along with authors of the educational area, make the epistemological space of this study. The experience of the teachers is permeated by ambiguous feelings, witch receive new meanings as they visualize the results of their work on inclusion of SSEN. These teachers demonstrated to conceive the inclusion as a tough reality, which they do not know, exactly, how to deal with. We analyzed the linking of this fact with the concept of self, since it is a basic element of the behavior and the way they perceive the world around. The reached conclusions led to conceived that to be professor in the scene of the inclusive school demands an open minded profile, in order to accept and to receive the other in its difference, making possible learning opportunities to the student, as well as to the professor. This coexisting became a source of practical renewal and chance of personal growth, throughout a self-knowledge process for teachers. With this inquiry we perceive that, for the teachers of the study, the inclusion constitutes in a great challenge to be surpassed, and the relationship with SSEN can change the way of perceiving and, consequently, is related to the phenomenon of the deficiency in the context of the inclusive school, where the professor is invited, constantly, to the creation and re-invention of his actions and itself.